PEMBAGIAN WARIS BAGI WANITA DALAM HUKUM WARIS ADAT BALI SETELAH DIKELUARKANNYA KEPUTUSAN PASAMUAN AGUNG III MUDP BALI NO. 01/KeP/PsM-3/MDP BALI/X/2010 DI KECAMATAN BULELENG KABUPATEN BULELENG BALI - , Desy Erina ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The objective of this research is to observe the judicial review to find out about the process of decision making. Division, and the solution in case there is a inheritance dispute for woman after the issuing of the Edict of Great Gathering (Pesamuan Agung) III MUDP Bali No. 01/Kep[/Psm-3/Mdp/X/2010 in the District of Buleleng. This is a empirice-judical research- a research using the primer data, namely the main data which was obtained from field study which is augmented with library study. Primary data was obtained through interview, with 18 respondents and 7 sources person, determined by purpose sampling. The secondary data was obtained from literature. Then the obtained data was broken down and analyzed The result of the study showed that : (1) The process of the issuing of the edict of The Great Gathering III MUDP Bali No. 01/Kep/Psm-3/Mdp Bali /X2010 was preceded from the writing of the edict draft by The Main Council of Customary Village . Later on the Main Council of Customary Village conducted a socialisation regarding.The draft of the edict, requesting opinions from customary public figures, and and those who are interested in woman affairs, the last activities were conducting a working meeting (pesamuan) in order to make the draft of edict of Great Gathering III in question would be legal and goes into effect. In the Great Gathering III concerned has been decided that female child has a limited right to inherit of her parentâs possession namely 2:1 (2). In the District of Buleleng the distribution of heritage is implemented before and after the death of the inheritor, the division of heritage woman in one family and the other families are having different system respectively with different division. The trend is that the division of male child is bigger. The division is not based on what is regulated in the Edict of Great Gathering III MUDP Bali No. 01/Kep/Psm- 3/Mdp Bali X 2010. (3). Solution of problem in case there is a dispute. is not only can be solved through law process (Court) but it can also be solved through family consensus and customary consensus.